Antimicrobial effect of the quitosano and rind of orange in the treatment of waste water - Campo Vera, Yesenia (2017)
Chitosan and its derivatives as natural antimicrobial agents can be applied in agriculture, and in the food, biomedical, biotechnological and pharmaceutical industry. Its antimicrobial activity depends on many factors such as its molecular size, source, associated components, pH, concentration and the type of microorganism. Orange peels are a bio absorbent of ecological nature low-cost and easily found. The research aims to assess the antimicrobial effect of chitosan and aqueous extract or orange peels in different concentrations for the treatment of waste waters. The chitosan was obtained in its commercial presentation (Ch) of low molecular weight with a deacetylation (DA) degree of 81.4%, and the orange peels were treated by air-drying and later pulverization. During the essay, Gram positive and Gram negative bacteria were isolated and identified from the samples of waste water taken from the final emitter in the waste water treatment plant in the municipality of Saravena, Colombia; and the inhibition percentage was determined through antibiogram tests. Results showed that Gram positive bacteria are more sensitive to treatment than Gram negative bacteria. The combination of chitosan and aqueous extract of orange peels (at a 50%-50% ratio) caused a significant increase in the inhibition percentage, showing that orange peels bolster the antibacterial activity of chitosan and make it an eﬃcient agent to be used in the treatment of waste waters.